A clinical study of commonly isolated organism and its antibiotic sensitivity in diabetic foot ulcers in Sri Manakula Vinayagar Medical College and Hospital, Pondicherry - Shanmugaiah, Anand; Pandian, Saravanan; Selvam, Sudha (International Surgery Journal, 2020)
Background: Diabetic foot ulcer is one of the major surgical problem leading to hospital admission. Diabetic foot ulcer patients with uncontrolled diabetes may end up in forefoot amputation. Early aggressive debridement, control of blood sugar and empirical antibiotic therapy would reduce the morbidities in patients with diabetic foot ulcer. Further the knowledge of commonly isolated microbes and their antibiotic sensitivity pattern would be helpful to start empirical therapy. The purpose of this study was to determine the microbiological proﬁle of diabetic foot infections (DFIs) and assess the antibiotic susceptibility of the causative agents. Methods: This cross-sectional study was conducted in 115 patients admitted with diabetic foot ulcer over a period of 9 months from October 2015 to June 2016 at the department of general surgery, Sri Manakula Vinayagar Medical College and Hospital, Pondicherry. Tissue scrapping samples were collected and processed as per standard guidelines. Results: 167 organisms were isolated from 115 patients. 52% of culture showed polymicrobial growth. There was increased prevalence of gram-negative organisms 53% compared to gram positive organisms 47%. When comes to individual isolate, Staphylococcus aureus was the most common organism isolated 24.6% followed by Pseudomonas aeruginosa 21%. All gram-positive aerobes were sensitive to vancomycin and gram-negative isolates were sensitive to amikacin, piperacillin-tazobactum, gentamycin and cefotaxime. Conclusions: Staphylococcus aureus and Pseudomonas were the common pathogens isolated. This study recommends use of vancomycin along with piperacillin-tazobactum as an empirical therapy along with adequate blood sugar control and early debridement of devitalized tissues in patients with diabetic foot infections.